2019
DOI: 10.1038/s41598-019-56036-3
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA AURKAPS1 potentiates malignant hepatocellular carcinoma progression by regulating miR-142, miR-155 and miR-182

Abstract: The mitotic serine/threonine kinase aurora kinase-A (AURKA) has been identified as carcinogenic in hepatocellular carcinoma (HCC). AURKAPS1, a long non-coding RNA (lncRNA), is the pseudo-gene of AURKA, which play important roles in the cancer. Its underlying functions and mechanisms in liver cancer progression remain largely unknown. The mRNA expression of AURKAPS1 in HCC tumor tissues was significantly higher, which is associated with tumor size and TNM stage. The high expression of AURKAPS1 promotes cell mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…The cross-regulation between lncRNAs and miRNAs has been demonstrated. lncRNAs may serve as ceRNAs to modulate the expression and functions of miRNAs, and thus have been termed are ‘miRNA sponges’ ( 32 , 33 ). To understand the potential oncogenic mechanisms of LINC00665 in glioma cells, the starBase bioinformatics database was utilized to identify miR-34a-5p as a target of LINC00665 .…”
Section: Discussionmentioning
confidence: 99%
“…The cross-regulation between lncRNAs and miRNAs has been demonstrated. lncRNAs may serve as ceRNAs to modulate the expression and functions of miRNAs, and thus have been termed are ‘miRNA sponges’ ( 32 , 33 ). To understand the potential oncogenic mechanisms of LINC00665 in glioma cells, the starBase bioinformatics database was utilized to identify miR-34a-5p as a target of LINC00665 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, some lncRNAs were demonstrated to be deregulated in LCSCs and HSCs and could cause the activation of HCC initiation and fibrosis, such as HULC and ANRIL [61,62]. Likewise, lncRNAs can also participate in tumor growth and metastasis, through regulating EMT, cells proliferation and apoptosis [63][64][65]. Most of these lncRNAs could serve their functions by regulating the expression of target genes, including protein-coding genes or other non-coding RNAs [66].…”
Section: Lncrnas and The Mechanisms Of Hcc Tumorigenesismentioning
confidence: 99%
“…Li et al reported that AURKAPS1 expression in 124 cases of HCC tissues was significantly higher than in adjacent normal liver tissues. Additionally, the expression level of AURKAPS1 was positively correlated with tumor size ( p < 0.006) and TNM stage ( p < 0.046), confirming its carcinogenic role [ 171 ]. AURKAPS1 increased HCC cell migration and invasion through competitive binding to miR-142, miR-155, and miR-182, promoting the expression of their target RAC1.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the AURKA gene, AURKAPS1 has the absence of a 359–560 coding sequence region, and differences in the 3′-terminal nucleotide sequence and nucleotide mutations. To date, the function and abnormal expression of AURKAPS1 in cancerous tissues have been reported in few articles [ 171 ]. Li et al reported that AURKAPS1 expression in 124 cases of HCC tissues was significantly higher than in adjacent normal liver tissues.…”
Section: Introductionmentioning
confidence: 99%